The Concept of Risk in Biomedical Research Involving Human Subjects - Ness, Peter H. Van (Bioethics, 2001)
An established ethical principle of biomedical research involving human subjects stipulates that risk to subjects should be proportionate to an experiment’s potential benefits. Sometimes this principle is imprecisely stated as a requirement that ‘risks and benefits’ be balanced. First, it is noted why this language is imprecise. Second, the persistence of such language is attributed to how it functions as a rhetorical trope. Finally, an argument is made that such a trope is infelicitous because it may not achieve its intended persuasive purposes. More importantly, it should be avoided because it masks the important role that chance plays in clinical research. Risk is the possibility of harm. As a precondition of harm it is unintended and undesirable in projects of biomedical research. It requires ethical vigilance. As a vehicle of chance, however, it is both intended and desirable. It requires methodological appreciation.